Arang Kayu, Batok Kelapa, Kulit Durian Dan Kulit Pisang Sebagai Bahan Pengganti Resistor Film Karbon - Wisutama, Remanda Arya; Nurseptiani, Syifa; Azizah, Athirah Nur; Subagiyo, Lambang; Nuryadin, Atin (Journal BEARINGS: Borneo Mechanical Engineering and Science, 2022)
Indonesia’s dependence on imported resistors must be addressed. Producing domestic resistors and using cheaper, more efficient materials is one way to reduce it. The purpose of this study was to determine the specific resistances of carbon film resistors produced from several natural materials. The carbon film resistors were made from 4 different charcoal materials: wood, coconut shells, banana peel, and durian peel charcoals. The fine natural charcoals were put into straws with different cross-sectional areas and lengths. The resistance was measured using a digital multimeter, and the specific resistance was subsequently calculated. The highest specific resistance was obtained by wood charcoal of 8.68x106Ωm, then followed by coconut shell charcoal, durian peel charcoal, and banana peel charcoal, which were 7.23x106Ωm, 4.91x106Ωm, and 4.37x106Ωm, respectively. Based on this research, wood, coconut shell, banana peel, and durian peel charcoals have the potential to be used as alternative materials to replace carbon film resistors.